Exploring the key facets of leakage dynamics in water distribution networks: Experimental verification, hydraulic modeling, and sensitivity analysis. (15th August 2022) - Zaman, Dina; Gupta, Ashok Kumar; Uddameri, Venkatesh; Tiwari, Manoj Kumar; Sen, Dhrubajyoti
Abstract: Hydraulic solvers are extensively used for the real-time operational analysis and asset management of water distribution networks. However, the influence of leakage on network hydraulics is still not fully understood, and limited experimental verification concerning leakage modeling and calibration efficacy of hydraulic solvers is presently available. To address these limitations, this research develops a novel strategy to quantitatively assess the efficacy of the popular hydraulic solver, EPANET 2.0 in emulating the leakage dynamics through an extensive experimental study conducted on a realistic sensor-equipped network prototype followed by comprehensive leakage modeling and analysis. The network response to diverse leak scenarios is experimentally analyzed, and the inferences derived are utilized to configure the leak models. A stage-wise calibration routine of the base and leak models is executed, which exhibits reasonable accuracy with mean absolute errors of 0.011 and 0.060, respectively. The calibrated leak models manifest satisfactory performance concerning the simulated system pressure and effectively predict the leak flow trends at all leakage levels. The sensitivity matrix of the leak models also captures the variation in the localized and global impact of leak levels on system flow and pressure concerning different leak scenarios. Thus, this research experimentally verifies the efficacy of leakage modeling using EPANET 2.0 and delineates the potential challenges concerning efficient calibration and performance analysis of leak models using the predefined leak parameters. The implications of this study can be instrumental for utility managers and researchers in configuring improved leak models using hydraulic solvers and strategizing model-based leakage management plans. Graphical abstract: Image 1 Highlights: Diverse leak experiments on a realistic sensor-equipped network prototype conducted. The leakage modeling efficacy of hydraulic models built in EPANET 2.0 assessed. Calibration of leak models using emitter coefficients and exponents executed. Model performance reasonably predicted the hydraulic variables during leakage. Sensitivity matrices of leak models effectively captured the impact of leakage.